Reduced electroencephalographic coherence asymmetry in the Chernobyl accident survivors - Zhavoronkova, Ludmila A.; Kholodova, Nina B.; Belostocky, Alexey P.; Koulikov, Mikhail A. (The Spanish Journal of Psychology, 2008)
An electroencephalograph (EEG) study was carried out from 1990 to 2006, using power spectra, averaged coherence, and integral EEG coherence asymmetry coefficients to compare 189 clean-up workers of the Chernobyl accident with 63 age matched healthy controls. Most of the Chernobyl workers showed three abnormal EEG patterns, as indicated by EEG power mapping. The higher power, most prominent in slow alpha and theta bands, or in fast alpha frequencies, were observed in persons 3-5 years after the clean-up works (the early stage). The lower EEG power in alpha band was found in Chernobyl workers 10 or more years after the accident (the late stage). EEG coherence analysis revealed the existence of two stages in EEG alterations following the Chernobyl clean-up. In the early stage, an increase of EEG coherence in the central brain areas was observed, whereas at the later stage, a decrease of EEG coherence, most prominent in the frontal brain areas, and reduced brain asymmetry prevailed. These results allow us to propose that the described EEG signs may be a reflection of radiation-induced brain dysfunction at the late period after the Chernobyl clean-up and were similar to the EEG markers of brain ageing. The results, in comparison to data of the literature, provide additional support to the premature brain ageing hypothesis in Chernobyl survivors as a result of the radiation brain damage after-effect.